Petrogenesis of the New Amalfi sheet a highly differentiated Karoo intrusion - Williams, Craig Milton (Rhodes University, Faculty of Science, Department of Geology, 1995)
The New Amalfi Sheet is a highly differentiated tholeiitic intrusion which is situated between the towns of Matatiele and Swartberg in East Griqualand. It lies within the Central area of the Karoo Igneous Province. Rock types range from dolerites at the base and top through to a highly differentiated granophyre which is found as a 'sandwich horizon' within the top half of the sheet. The most evolved granophyre represents 15.86% of the initial liquid, which was found to be very similar in composition to the average Lesotho-type magma of Marsh and Eales (1984). The paragenetic sequence was found to be chromite → olivine → plagioclase → pigeonite and augite. Cumulus magnetite and ilmenite enter the paragenetic sequence together with immiscible sulphide droplets after 35% crystallization. In the late stages of crystallization, augite changes composition towards ferrohedenbergite. The reappearance of iron-rich olivine coincides with the disappearance of pigeonite and apatite appears as a cumulus phase for the first time after 70% crystallization. Granophyric intergrowth, which contains coarse perthitic Kfeldspar, becomes the most abundant modal entity within the most evolved granophyres. Differentiation was dominated by fractionation of plagioclase and pyroxene, with subordinate olivine and opaque-oxide fractionation. A minor amount of assimilation of country rock occurred within the topmost granophyres. The intrusion has been dated, using the Rb-Sr isochron method, at 178.37 ± 5.52 Ma. Extensive subsolidus deuteric alteration has resulted in the formation of a complete series of hydrothermally altered clinopyroxenes which are enriched in CaO but depleted in TiO₂ compared to the unaltered magmatic clinopyroxenes. It has also resulted in the formation of abundant vermiform ilmenite in the most evolved rocks, recognized by the fact that this phase is enriched in MnO compared to magmatic ilmenites. The very iron-rich orthopyroxene, ferrohypersthene, was found to have crystallized, during cooling of the sheet from the intercumulus liquid. Olivine in the dolerite re-equilibrated with the intercumulus liquid, becoming more iron-rich in composition.
Keywords: Petrogenesis -- South Africa -- Eastern Cape -- Karoo; Geochemistry -- South Africa -- Eastern Cape -- Karoo